2013
DOI: 10.1002/ajp.22141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Cognitive Challenge Device Containing Food and Non‐Food Rewards on Chimpanzee Well‐Being

Abstract: Exploration and problem-solving are highly motivated behaviors in non-human primates, but little research has focused on whether cognitively challenging tasks can enhance primates' psychological well-being, particularly in the absence of food rewards. We evaluated whether a novel cognitive challenge device (CCD) consisting of a maze of opaque tubes enhanced the well-being of a group of six adult chimpanzees housed at ZSL Whipsnade Zoo, UK, over a two-month period. Chimpanzees had the opportunity to interact wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 43 publications
0
47
1
Order By: Relevance
“…Clark and Smith (2013) found that chimpanzees exhibited more problem-solving behaviors and spent significantly more time engaged in social play when the maze was present; the maze was also used significantly more when it contained wooden tokens (which could not be physically accessed) compared with food items (nuts, which could be physically accessed). On the basis of these results, Clark and Smith (2013) felt there was some evidence for cognitive enrichment, but a small sample size (six individuals) made it difficult to draw strong conclusions. found that a group of six male dolphins spent significantly more time underwater when the underwater maze was present; it challenged cognitive skill through the stimulation of new problem-solving strategies and also stimulated social play.…”
Section: Cognitive Enrichment Attempts In Captive Settingsmentioning
confidence: 97%
See 4 more Smart Citations
“…Clark and Smith (2013) found that chimpanzees exhibited more problem-solving behaviors and spent significantly more time engaged in social play when the maze was present; the maze was also used significantly more when it contained wooden tokens (which could not be physically accessed) compared with food items (nuts, which could be physically accessed). On the basis of these results, Clark and Smith (2013) felt there was some evidence for cognitive enrichment, but a small sample size (six individuals) made it difficult to draw strong conclusions. found that a group of six male dolphins spent significantly more time underwater when the underwater maze was present; it challenged cognitive skill through the stimulation of new problem-solving strategies and also stimulated social play.…”
Section: Cognitive Enrichment Attempts In Captive Settingsmentioning
confidence: 97%
“…Furthermore, problem-solving tasks without the incorporation of an extrinsic food reward are exceptional in a zoo setting. To address this, Clark and colleagues (Clark & Smith, 2013; designed cognitive challenges for socially-housed chimpanzees (Pan troglodytes) and bottlenose dolphins (Tursiops truncatus) that were intended to provide abstract problems (3D vertical mazes solved using the hands or rostrum respectively) and could be tested with and without extrinsic rewards. They were inspired by laboratory cognitive tests (e.g., great ape trap tubes: Martin-Ordas, Call, & Colmenares, 2008; dolphin underwater modality apparatus: e.g., Herman, 2010), rather than by examples of previous enrichment for these taxa.…”
Section: Cognitive Enrichment Attempts In Captive Settingsmentioning
confidence: 99%
See 3 more Smart Citations